KONSERVASI DAN REVITALISASI BANGUNAN LAMA DI LINGKUNGAN KOTA DONGGALA - Mansur, Fathurrahman (MEKTEK, 2006)
The Old City of Donggala is a historical part of the city wich has very special colonial character. As such, it is a very valuable asset for the city, not just because of its buildings and artifacts but also because of its infrastructure. It has been designated as a main priority area for revitalization. It is a pity, however, that this priceless gem has been neglected for quite a long time, and its vitality is diminishing if not dying. Today the Old City has lost most of its function as the center of Donggala.The involution (due to poor urban development manage-ment practices) which forced the central business district to move from the old city to other part of the city has caused the decline of the area. This is market by the process of resident and business flights. The strategic importance of the Old City for economic and mixed-us function has gradually been diminished. Most of the land-use and space-use has changed. Some buildings have become storehouse , while others have been completely abandoned. The decline of the Old City made it lost it prestige as a place for offices, shops, cafes and other commercial activities as it was in the past. As business activities have dropped, so has the revenues coming into the area.